The audacity of hope thoughts on reclaiming the American dream - Obama, Barack; Bronstein, Jacob (New York : Random House Audio, 2006)
Senator Barack Obama reflects on the American ideals that led him into politics. Barack Obama has been hailed by voters of all stripes as a man of uncommon gifts and far-reaching vision. In'The audacity of hope', he draws on his personal experience as a senator and lawyer, professor and father, Christian and skeptic, and finds a shared language about our nation's values. At the same time he explores the gap between our American ideals and the ruthless imperatives of today's politics
Title from container
Keywords: Obama, Barack; Obama, Barack -- Philosophy; Legislators -- United States -- Biography; African American legislators -- Biography; National characteristics, American; United States -- Politics and government -- Philosophy; United States -- Politics and government -- 2001-2009